OCA Java SE 8 programmer I study guide (exam 1Z0-808) - Finegan, Edward; Liguori, Robert (Online access with DDA: Askews (Maths), 2016)
The definitive Oracle Press guide to the latest release of this entry-level certification for Java programmers.